The Internet, social capital and local community - Ferlander, Sara (2003)
This dissertation is concerned with the extent to which the use of information and communication technology can (re-)create social capital and local community in an urban environment. Will the new technologies lead to new forms of social inclusion or to the creation of a digital divide? How have social networks, social support, trust and sense of community been affected by the rapid development of the Internet? In the literature there is disagreement between writers who see the technology as a new basis for social inclusion, social capital and community (e. g. Wellman, 1997; Rheingold, 2000; Lin, 2001) and others who see it as a threat, leading to new forms of exclusion and a decline in face-to-face contacts ( e.g . Slouka, 1995;Stoll, 1995). A combination of qualitative and quantitative data from a study in a relatively disadvantaged area of Stockholm is used to evaluate the impact of two computer projects, a Local Net and an Internet Cafe. Each of the projects was aimed at encouraging digital inclusion and at enhancing social contacts and the sense of community. The findings show that Local Net largely failed to achieve its goals and was abandoned two years after its inauguration. In its place an Internet Cafe was established, which seems to be achieving many of the goals that were set out in its prospectus. Visitors to the Cafe, who include many representatives of disadvantaged groups, have acquired useful computer skills. The IT-Cafe, with is provision of subsidised public access, in formal support and training, makes its visitors feel more included in the Information Society as well as in the wider society. The visitors also have more local friends, express stronger social trust and perceive less tension in the than non-visitors. The Internet Cafd is regarded as an offline as well as online meeting-place with positive impacts on social integration, and Internet use is associated with networking, exchange of support and information seeking